Potential-step chronocoulometry for robust analysis of charge-transport and thermoelectric behaviors of conducting polymers - Imae, Ichiro (Frontiers in Materials, 2025)
Since the groundbreaking discovery of polyacetylene films in the 1960s and subsequent efforts to enhance their electrical conductivity through halogen doping, several conductive π-conjugated polymers have been developed and applied in the fabrication of smart windows, organic photovoltaic cells, lithium-ion batteries, and other optoelectronic and electrical devices. Recently, the potential of these polymers for use in thermoelectric devices toward waste-heat recovery has drawn considerable attention. Given that the electrical properties of conducting polymers are strongly influenced by their doping state, the precise control of this state and accurate estimation of the doping level (charge density, i.e., the number of injected charges per unit volume) are of high importance. This review outlines the methods used to precisely control the doping state of conducting polymers and accurately determine their charge density, with a focus on potential-step chronocoulometry (PSC). Moreover, this paper highlights the recent progress in the application of PSC for analyzing charge-transport and thermoelectric properties. Challenges remain in the quantitative accuracy of electrochemical measurements, the applicability to a broader range of polymers, and the ability to distinguish between different charge carriers. Future research could resolve these issues and lead to improved understanding of charge transport and thermoelectric properties, paving the way for the development of advanced materials for thermoelectric applications.